A distributed polling service‐based MAC protocol testbed‡. (12th June 2013) - Huang, Yingsong; Walsh, Phillip A.; Li, Yihan; Mao, Shiwen
SUMMARY Medium access control (MAC) protocols play a vital role in wireless networking. It is well‐known that the high control overhead of IEEE 802.11 MAC is the limiting factor on the throughput and delay performance of wireless networks. In our prior work, three polling service‐based medium access control protocols (PSMACs) are developed to amortize the high control overhead over multiple frame transmissions, thus achieving higher efficiency. Both analysis and simulations are conducted to validate the efficacy of the proposed protocols. In this paper, we extend this work by implementing the distributed version of PSMAC, i.e., PSMAC 2, on the GNU Radio and universal software radio peripheral (GNU Radio/USRP) platform. We discuss various design considerations and challenges of prototyping PSMAC 2 and carry out extensive experimental studies with the GNU Radio/USRP PSMAC testbed. Our experimental results are found to be consistent with the theoretical study reported in our prior work and validate the advantages of PSMAC under a realistic wireless channels. Copyright © 2013 John Wiley & Sons, Ltd.